Agro-Climatic Regional Planning Project - Planning Commission (Planning Commission, Government of India, 1995)
The Agro-Climatic Regional Planning (ACRP) Project, initiated by the Planning Commission in 1988, represents a strategic shift in India’s agricultural planning paradigm toward a resource-based, region-specific, and sustainability-oriented framework. By delineating the country into 15 agro-climatic regions and 73 sub-regions, the project integrates environmental, socio-economic, and technological dimensions to address regional disparities in agricultural productivity and resource utilization. Moving beyond the earlier emphasis on extensive growth and technology-driven expansion associated with the Green Revolution, ACRP seeks to harmonize productivity enhancement with ecological balance and social equity. The initiative emphasizes efficient resource use through soil and water conservation, rehabilitation of degraded lands, and diversified agricultural systems that include both crop and non-crop activities such as livestock rearing and agroforestry. Zonal Planning Teams comprising multidisciplinary experts are tasked with assessing regional resource endowments, identifying agricultural priorities, and formulating financially viable and socially relevant action plans. By institutionalizing decentralized planning and stakeholder participation, ACRP aims to create replicable development models that align short-term productivity goals with long-term environmental sustainability. Overall, the project lays a comprehensive foundation for balanced agricultural growth, ensuring food security while preserving ecological integrity and promoting inclusive rural development across India’s diverse agro-climatic landscapes.
Agro-Climatic Regional Planning Unit Sardar Patel Institute of Economic & Social Research Ahmedabad
Agro-Climatic Regional Planning Unit Sardar Patel Institute of Economic & Social Research Ahmedabad
Keywords: Agro-Climatic Regional Planning; Resource-Based Agricultural Development; Sustainable Agriculture Strategy; Planning Commission Initiative 1988; Regional Disparity Reduction; Environmental Sustainability; Green Revolution Transition; Integrated Farming Systems; Soil and Water Conservation; Zonal Planning Teams; Agroforestry Promotion; Institutional Framework for Rural Development